Notes from the Field of the Scholar–Practitioner: Inhabiting the Liminal Space between Research and Practice—A Reflective Account of Holding Dual Identities - Kirsten Stevens-Wood; Kate Attfield (Societies, 2024)
Kirsten and Kate are scholar–practitioners studying the people with whom they interact and operate. In this empirical paper, based on their auto/ethnographic reflections, they study some often-neglected circumstances and by-products of scholar–practitioner research. They review aspects of entering research situations with which they are connected, participating in them, leaving them behind, and revisiting them. Kirsten is an ethnographer, both working with and studying intentional communities. Kate is a qualitative researcher who operates auto/ethnographically in studying Triple X unintentional communities. This article arises from discussions of Kirsten’s and Kate’s field notes, which have led them to compare and relate their convergent experiences with one another. Kirsten and Kate focus on the physical culture of the environments in which they study. Some traditional boundaries like the isolation of researchers and communities are eroding. Kirsten and Kate care about those they study and continue to hold some responsibility for the lives of people they have entered. They attempt to narrow the space between theory and practice in recognising their interconnected nature. Civic mission is gaining increased currency for researchers and may form a signpost towards the future of research.